Level of Income and the Investment Development Path Theory: Evidence From Africa - Justice G. Djokoto (SAGE Publishing, 2021)
The investment development path theory delineates countries in stages I, II, III, IV, and V according to the level of development as developing, transition, and developed countries. The World Bank’s classification of countries by income, however, identifies countries as lower-income, lower-middle-income, upper-middle-income, and high income. In this paper, we test the investment development path theory for countries based on the level of income using data from 1980 to 2019. Africa offers unique data as it is the only continent made up of entirely developing countries together with countries that fit into all four classifications based on income. Income level classifications appear to enhance the position of countries within the investment development path ahead of that based on the United Nations classification. The use of income classification should complement that of the United Nations in the empirical testing of the investment development path theory for a more current investment development path status.